Effect of an exercise program on musculoskeletal symptoms in primary school teachers - Manrique-Collantes, Rosmery V. (2020)
Introduction. Primary-level teachers are exposed to physical risks that they can control through an exercise program, which seeks improved promotions for their health in a timely manner. Objectives. To determine the effect of an exercise program on the musculoskeletal symptoms in primary school teachers. Methods. An experimental study was carried out, where the Cornell questionnaire was applied. Results. The teachers had a median age of 52 years. Initially, it was found that the most frequent musculoskeletal symptoms of all teachers were found in the neck (50,8%), lower back (41,5%), left foot (35,4%) and right foot (33,9%); in the final comparison between the groups, it is observed that the intensity obtained significant differences of p value <0,01 for neck, right/left shoulder, upper back, lower back, right/left knee. It is worth noting in the difference in initial and final data, the intervention group obtained 25% or more for the neck, lower back, right/left shoulder and right foot areas; while in the control group, 18,2% would worsen in the lower back area. Conclusions. The exercise program frequently improves the musculoskeletal symptoms of the teachers in the intervention group, while in the control group similar or are used or increase.